At Westonci.ca, we make it easy to get the answers you need from a community of informed and experienced contributors. Join our Q&A platform and connect with professionals ready to provide precise answers to your questions in various areas. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.

Write the simplified expression: 2x + 3(x - 2) - 3(x -6)

Sagot :

Answer:

2x+12

Step-by-step explanation:

2x+3(x−2)−3(x−6)

Distribute:

=2x+(3)(x)+(3)(−2)+(−3)(x)+(−3)(−6)

=2x+3x+−6+−3x+18

Combine Like Terms:

=2x+3x+−6+−3x+18

=(2x+3x+−3x)+(−6+18)

=2x+12

Answer:

=2x+12

Answer:

2x + 12

Step-by-step explanation:

distribute numbers inside parentheses

2x + 3x -6 -3x + 18

add x values together and integers together

2x + 3x -3x = 2x

-6 + 18 = 10

simplified to 2x + 12